The Recent Archaeology of the Early Modern Period in Quebec City: 2009. - Moss, William, author.
1 online resource
Keywords: "This volume is the result of collaboration between SPMA and the Association des archeologues du Quebec (AAQ); its guest editor is William Moss, Chief Archaeologist for the City of Quebec. The publication has arisen from the celebration of the 400th anniversary of the city's founding by Samuel de Champlain in 1608, an occasion which gave momentum to a number of important archaeological projects in the city and surrounding region, and provided an excellent opportunity to present their results. It contains sixteen papers, all translated from French, the language of Quebec City. They include accounts of exciting discoveries relating to the port, the great chateau on the crag above it, the defences, and the newly discovered remains of the short-lived colony of the 1540s. The papers underline Quebec's status as one of the leading centres of urban research in North America. The volume provides the only modern overview of archaeological work in the city in the English language."